Increased Contractile Function of Human Saphenous Vein Grafts Harvested by “No-Touch” Technique - Vestergaard, Lene P.; Benhassen, Leila; Modrau, Ivy S.; de Paoli, Frank; Boedtkjer, Ebbe (Frontiers in Physiology, 2018)
Saphenous vein grafts are the most common conduits used for coronary artery bypass grafting (CABG); however, no more than 60% of vein grafts remain open after 10 years and graft failure is associated with poor clinical outcome. The ‘no-touch’ harvesting technique—where a sheet of perivascular tissue is retained around the vein—improves graft patency to over 80% after 16 years of follow-up, but the mechanism for the improved patency rate is unclear. In this study, we investigated acute functional differences between vein grafts harvested conventionally and by ‘no-touch’ technique and explored the importance of perivascular tissue for reducing surgical trauma, minimizing excessive distension, and releasing vasoactive paracrine factors. Segments of human saphenous veins were obtained from CABG surgery and their functional properties investigated by isometric and isobaric myography. We found a broad diameter-tension relationship for human saphenous veins, with peak capacity for active tension development at diameters corresponding to transmural pressures around 60 mmHg. Across the investigated transmural pressure range between 10 and 120 mmHg, maximal tension development was higher for ‘no-touch’ compared to conventionally harvested saphenous veins. Contractile responses to serotonin, noradrenaline, and depolarization induced with elevated extracellular [K+] were significantly larger for saphenous veins harvested by ‘no-touch’ compared to conventional technique. Conventional vein grafts are routinely pressurized manually in order to test for leaks; however, avoiding this distension procedure did not change the acute contractile function of the conventionally excised saphenous veins. In contrast, even though surgical removal of perivascular tissue during conventional harvesting was associated with a substantial decrease in force development, removal of perivascular tissue by careful dissection under a stereomicroscope only marginally affected contractile responses of veins harvested by ‘no-touch’ technique. In conclusion, we show that saphenous veins harvested by ‘no-touch’ technique have greater contractile capacity than veins harvested by conventional technique. The different capacity for smooth muscle contraction is not due to vasoactive substances released by the perivascular tissue. Instead, we propose that the larger tension development of saphenous veins harvested by ‘no-touch’ technique reflects reduced surgical damage, which may have long-term consequences that contribute to the superior graft patency.